2005
DOI: 10.1073/pnas.0505818102
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of the membrane-localized virulence activator TcpP by the YaeL protease in Vibrio cholerae

Abstract: A common mechanism inhibiting the activity of transcription factors is their sequestration to the membrane until they are needed, at which point they are released from the membrane by proteolysis. Acting in contrast to this inhibition mechanism are virulence regulators of Vibrio cholerae, the ToxR and TcpP proteins, which are localized to the inner membrane of the cell, where they bind promoter DNA and activate gene expression. TcpP is rapidly degraded in the absence of another protein, TcpH. We used a genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
132
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(141 citation statements)
references
References 34 publications
(68 reference statements)
9
132
0
Order By: Relevance
“…S3B). We found that bile salts had no effect on TcpP stability, and that TcpA protein production was dependent on the presence of TcpH only if YaeL was also present, as has been previously reported (14).…”
Section: Identification Of Taurocholate As One Of the Host Virulence-supporting
confidence: 67%
See 1 more Smart Citation
“…S3B). We found that bile salts had no effect on TcpP stability, and that TcpA protein production was dependent on the presence of TcpH only if YaeL was also present, as has been previously reported (14).…”
Section: Identification Of Taurocholate As One Of the Host Virulence-supporting
confidence: 67%
“…2C). TcpP is known to be rapidly degraded through proteolysis by the protease YaeL in the absence of a second protective protein, TcpH (14). To test whether bile salts affect TcpP stability through TcpH, we examined the bile salt effects on TcpP stability ( Fig.…”
Section: Identification Of Taurocholate As One Of the Host Virulence-mentioning
confidence: 99%
“…We have suggested that RseP cleavage of full-length RseA is blocked so that DegS cleavage of RseA will be rate-limiting over a wide range of OMP signal. Interestingly, other RIP proteases that are widely used to transmit signals via a protease cascade between the compartments of a bacterial cell appear to occupy an intermediate position in every cascade: They transmit the signal rather than initiate the cascade and their activity is inhibited until the initial cleavage event is completed (Schobel et al 2004;Chen et al 2005;Matson and DiRita 2005). Cells use widely different proteins to accomplish inhibition; it remains an open question as to whether these inhibitory events are mechanistically similar or distinct (Resnekov and Losick 1998;Dong and Cutting 2003;Kroos 2004, 2005).…”
Section: Organization Of the Proteolytic Cascadementioning
confidence: 99%
“…TcpPH, along with constitutively expressed ToxRS, activates transcription of toxT, resulting in colonization and CT secretion in a temporally coordinated fashion (13). Under noninducing conditions, TcpP is specifically targeted for degradation by the site 1 periplasmic protease, Tsp, followed by the membrane-localized metalloprotease YaeL (10,14,24).TcpP and ToxR have three distinct domains: an N-terminal cytoplasmic DNA-binding domain, a single membrane-spanning domain, and a C-terminal periplasmic domain. The cytoplasmic domain of TcpP and ToxR is homologous to that of the OmpR/ PhoB family of w-HTH transcription factors (15).…”
mentioning
confidence: 99%